“Eu não pago 60 mil por uma moto. Por uma Harley eu pago.” : análise do consumo da imagem simbólica - Weber, Karina Pereira (2015)
This research has as aim the comprehension of symbolic images by the relation with the hyper mark Harley-Davidson, starting with a presupposition that this images drive a kind of image consumption of the brand, as we purposed to think. The theoretical basis of the research consists of the basic notions of the imaginary, Gilbert Durand’s symbolic image; anthropological comprehension of the image and its production by the Hans Belting’s elucidations; comprehension of the brands and the consumption in the contemporary context by Gilles Lipovetsky and the comprehension of the consumption and it’s aspects beyond the objects with the Jean Baudrillard reflections’ help. The methodological path followed was the Michel Maffesoli’s Comprehensive Sociology, and Tim May and Maria Eugênia Costa’s Facal Group research technique. We see that the symbolic image emanating from the “individual-brand” transforms the way of consumption, which is a way to be explored by the branding as a way of providing transcendence relationship with brands.